Analysis of ISO 9001:2015 Implementation in Truck Body Check Section Case Study at PT. XYZ - Wilujeng Nugroho, Handi; Alawiyah Siregar, Erin (Journal of Engineering Science and Technology Management (JES-TM), 2021)
PT. XYZ is a company engaged in the body truck industry, both cold diesel and fuso. The application of ISO 9001:2015 in a company is one of the most important quality management principles because a result to be achieved will be more efficiently achieved when related activities and resources are managed as an integral process that cannot be separated.Therefore, the purpose of this study is to find out the efforts to implement the ISO 9001:2015 standard carried out by the checking section at PT. XYZ in the field based on indicators that have been determined by ISO 9001-2015 regarding quality. And after comparing and knowing the indicators that are appropriate and which are not in accordance with their application, it can be seen that all indicators are in accordance with the application in the field with a total percentage of 84.0%, and in this indicator the most significant is found in indicator III with a percentage of 86.2 % which is declared very good and indicator VI with a percentage of 88.9% which is declared very good. From the conclusions obtained. Based on the analysis of the overall percentage results, 8 indicators of the implementation of ISO 9001-2015 in the checking section of PT. XYZ can be categorized as "Very Good", because from the overall percentage of 8 indicators of the implementation of ISO 9001-2015, the percentage is 84.0%. And the suitability of the application in the company is in accordance with ISO 9001-2015.